Rapid, de novo development of isolated intracranial rosai-dorfman disease: A case report. (2nd January 2015) - Reynolds, Matthew R.; Sweeney, Kieron J.; Crilly, Shane M.; Farrell, Michael; Jaffe, Elaine S.; Javadpour, Mohsen
Abstract: Isolated intracranial Rosai-Dorfman Disease is rare. Here, we describe a patient who developed an asymptomatic, right parietal RDD lesion over 18 months while being followed radiographically for another brain lesion. To our knowledge, rapid, de novo radiographic formation of isolated intracranial RDD has never been reported in an asymptomatic patient.